Examining 5 types of evidence in article 1866 of the civil code as a pillar of civil law enforcement in Indonesia - Kupang, Frisca Melati (Institute Of computer Science (IOCS), 2025)
This research examines the use of five categories of evidence as defined in Article 1866 of the Civil Code (KUH Perdata) in the digital age, particularly electronic evidence as a legitimate form of proof. This research also outlines legal and practical challenges in employing non-traditional evidence in Indonesian civil justice. Normative legal study is descriptive and juridical-analytical. Along with associated rules and regulations, periodicals, legal literature, and comparative studies of other nations' legal systems are employed. The research found that although Article 1866 of the Civil Code provides a fundamental foundation for civil law evidence, the legal vacuum around electronic evidence produces legal ambiguity and inconsistency in court application. Lack of technical rules for digital evidence authentication, judge interpretation variances, and law enforcement technological competence are further challenges. Legal reform to incorporate electronic evidence, technical training for lawyers, technological infrastructure development, and Civil Code and Electronic Information and Transactions Law harmonization are suggested answers. This research offers an integrated strategy including all stakeholders to construct a civil law evidence system that is sensitive to contemporary changes and ensures justice and legal clarity for all parties